2010
DOI: 10.1111/j.1549-8719.2010.00053.x
|View full text |Cite
|
Sign up to set email alerts
|

Modulation by Cytochrome P450-4A ω-Hydroxylase Enzymes of Adrenergic Vasoconstriction and Response to Reduced PO2 in Mesenteric Resistance Arteries of Dahl Salt-Sensitive Rats

Abstract: Objective-This study evaluated the contribution of the 20-HETE/cytochrome P450-4A ω-hydroxylase (CYP4A) system to the early development of salt-induced vascular changes in Dahl salt-sensitive (SS) rats.Methods-CYP4A expression and 20-HETE production were evaluated and responses to norepinephrine, endothelin, and reduced PO 2 were determined by video microscopy in isolated mesenteric resistance arteries from SS rats fed high salt (HS; 4% NaCl) diet for 3 days vs. low salt (LS; 0.4% NaCl) controls.Results-CYP4A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 64 publications
1
8
0
Order By: Relevance
“…In our preparation, inhibition of 20-HETE production using 10 μM DDMS inhibited vasoconstriction to high oxygen tension in a reversible manner, but did not affect vasodilation to low oxygen tension (Figure 5). Previous studies have shown that vessels maintain their reactivity to vasoconstrictors (norepinephrine) following addition of DDMS [26], and in the present study the vessels maintained some tone after addition of DDMS. It is therefore unlikely that the lack of response to high oxygen reflects a general failure of the VSMC to contract.…”
Section: Discussionsupporting
confidence: 73%
“…In our preparation, inhibition of 20-HETE production using 10 μM DDMS inhibited vasoconstriction to high oxygen tension in a reversible manner, but did not affect vasodilation to low oxygen tension (Figure 5). Previous studies have shown that vessels maintain their reactivity to vasoconstrictors (norepinephrine) following addition of DDMS [26], and in the present study the vessels maintained some tone after addition of DDMS. It is therefore unlikely that the lack of response to high oxygen reflects a general failure of the VSMC to contract.…”
Section: Discussionsupporting
confidence: 73%
“…In an in vitro study [25], the vasodilatation of mesenteric arteries induced by ACh in low-sodium-fed rats was similar to that in high-sodium-fed rats. Another study [26] showed that the vasoconstrictive response of small mesenteric arteries to NA in low-sodium-fed rats was strong and comparable to that in high-sodium-fed rats. In an in vitro study using mesenteric resistance arteries [27], a high-sodium diet did not affect NA-induced vasoconstriction, but did impair ACh-induced vasodilatation.…”
Section: Discussionmentioning
confidence: 99%
“…As such, increases in the CYP4A/20-HETE system may be independent of dietary sodium. [1416] In order to determine the direct effects of salt on the CYP4A/20-HETE pathway independent of changes in arterial pressure, the present study evaluated the effect of short-term (three days) elevated dietary salt intake as the Dahl SS rat does not demonstrate salt-induced pressure changes within this limited time frame. [16] In addition, we evaluated vascular function in a novel cosomic rat strain (SS-5 BN ) carrying CYP4A alleles from the Brown Norway (BN) rat in the Dahl SS genetic background that exhibits dramatic attenuation of salt-sensitivity of blood pressure.…”
Section: Introductionmentioning
confidence: 99%